Meloside A Protects Dermal Papilla Cells from DHT-Induced Damage via Androgen Receptor Modulation - Hyun Jun Park; Bong Geun Song; Ji Hoon Song; Seung Hee Park; Da Hye Wang; Ho Kyun Kwon; Ji-Ean Lee (Current Issues in Molecular Biology)
Androgenetic alopecia (AGA) is associated with dihydrotestosterone (DHT)-induced apoptosis in human dermal papilla cells (HDPCs) via androgen receptor (AR) upregulation. This study aimed to evaluate the potential of Cucumis melo var. makuwa leaf extract (CLE) to attenuate these DHT-mediated effects in HDPCs. HDPCs were treated with CLE, and DHT-induced apoptosis and AR expression were assessed. High-performance liquid chromatography coupled with electrospray ionization tandem mass spectrometry (HPLC–ESI–MS) identified Meloside A as the principal bioactive constituent within CLE. CLE significantly attenuated DHT-induced apoptosis in HDPCs, demonstrating a 57.74% reduction at 1000 ppm. Mechanistically, Meloside A inhibited DHT-stimulated AR nuclear translocation and reduced AR protein expression. Furthermore, Meloside A decreased the expression of downstream target genes at 100 ppm, showing a 16.27% reduction in IL-6, a 26.55% reduction in TGF-β1, and a 35.38% reduction in DKK-1. Additionally, Meloside A significantly inhibited ROS generation within DHT-stimulated HDPCs by 45.45% at 100 ppm. These findings suggest that Meloside A, isolated from CLE, exerts anti-AGA effects by modulating AR nuclear translocation and gene expression. This highlights its potential as a therapeutic agent for AGA and provides a basis for developing novel therapeutic strategies for hair loss.